2015
DOI: 10.4209/aaqr.2015.03.0146
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the Dynamic Interactions and Exposure Implications of a Particle-Laden Cough Jet with Different Room Airflow Regimes Produced by Low and High Momentum Jets

Abstract: The objective of this study is to examine the dynamic interaction of a cough jet with different indoor airflow distributions created by linear slot diffusers considering the inter-personal transport of coughed particles. The experimental measurements were performed in a chamber, where the interaction of a cough jet and downward jets with various momentums was visualized by smoke. In this study, parameters related to the dynamic interaction of a transient cough jet and a steady downward jet have been studied: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…In order to evaluate dynamic airborne transmission, a suitable evaluation method is required. In the context of steady‐state conditions, there are two widely used methods for evaluating the risk of cross‐infection, namely intake fraction (IF) and exposure index ( ε s ) …”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In order to evaluate dynamic airborne transmission, a suitable evaluation method is required. In the context of steady‐state conditions, there are two widely used methods for evaluating the risk of cross‐infection, namely intake fraction (IF) and exposure index ( ε s ) …”
Section: Results and Analysismentioning
confidence: 99%
“…However, most tracer gas instruments, including the widely used photoacoustic gas monitor INNOVA, have a sampling time of the order of 10‐60 seconds, which is much longer than the period of inhalation or exhalation (which are of the order of 1 second). Aerosol generators have been increasingly used to provide a more accurate simulation of the transfer of exhaled droplet nuclei . However, they are mostly used alone (ie, not in conjunction with a manikin) and have a sampling interval of no smaller than 1 second .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 These velocities were in general higher than those measured in human subject studies, where the peak flow velocity during normal breathing was reported to be approximately 1-2 m/s. In general, the pulmonary ventilation rate and breathing cycle period of "standard persons" were used in past studies [3][4][5][6][7][10][11][12][13][14][15][16][17][18][19][20][21][22]30,31,33 of airborne cross-infection. In previous studies using breathing thermal manikins, a breathing cycle period of 6 seconds was usually assumed for a pulmonary ventilation rate of 6.0 L/min and 4 s for 10.0 L/min; the breathing cycle of 2.5 second inhalation, 2.5 second exhalation, and 1 second pause was most widely used, 11,12,30,31 although many studies used a cycle without a pause between exhalation and inhalation.…”
Section: Introductionmentioning
confidence: 99%
“…For the data under steady-state conditions, time-averaged mean values were calculated.The risk of cross-infection in steady-state conditions was indicated by the parameter exposure index (ε), which has been widely used in past studies [3][4][5][6]10,12,19,[45][46][47][48][49][50]. The FCM data were corrected for the time required for the N 2 O samples to travel in the sampling tube from the sampling location to the FCM monitors.…”
mentioning
confidence: 99%